Determinants of asthma in Ethiopia: age and sex matched case control study with special reference to household fuel exposure and housing characteristics - Yonas Abebe (BMC, 2021)
Abstract Background Asthma is a chronic inflammatory disorder characterized by airway obstruction and hyper-responsiveness. Studies suggest that household fuel exposure and housing characteristics are associated with air way related allergy. But there remains to be a considerable uncertainty about whether that reflects an association with asthma. This study endeavored to bridge the gap by identifying factors associated with asthma, with special reference to household fuel exposure and housing characteristics in selected public hospitals in Addis Ababa, Ethiopia. Methods We conducted a hospital-based matched case-control study. A total of 483 study participants were selected from two Ethiopian referral hospitals using a sequential sampling technique, with 161 cases and 322 controls. Standard questionnaire from the European Community Respiratory Health Survey II (ECRHS II) and the American Thoracic Society Division of Lung Disease (ATS-DLD-78) were used to collect household related data. Conditional logistic regression model was applied to identify the determinants of asthma. Both crude and adjusted odds ratios with 95% confidence interval (CI) were used to identify predictors of asthma. Results The response rate for both cases and controls was 99.17%. The odds of developing asthma was about four times higher among those who used agricultural residues for cooking (AOR: 3.81, 95% CI: 1.05, 13.79)., about five times higher among those who used wood for cooking (AOR: 4.95, 95% CI: 2.1, 11.69), nearly five times higher among those who had family history of asthma (AOR: 4.72, 95% CI: 1.54, 14.45), just over six times higher among those who smoke tobacco (AOR: 6.16, 95% CI: 1.31, 29.09) and over ten times higher among those who do not practice door opening, while cooking (AOR: 10.25, 95% CI: 3.97, 26.49). Conclusion Family history of asthma, tobacco smoking, use of solid fuels including, woods and agricultural residues were associated with development of asthma. To reduce the risk of asthma, people should practice door opening, while cooking, and must avoid using wood and agricultural residues for cooking and should also refrain from tobacco smoking.